Biodegradation of polyethylene and polypropylene by Lysinibacillus species JJY0216 isolated from soil grove. (September 2021) - Jeon, Jong-Min; Park, So-Jin; Choi, Tae-Rim; Park, Jeong-Hoon; Yang, Yung-Hun; Yoon, Jeong-Jun
Highlights: Lysinibacillus sp. JJY0216 isolated from soil degraded polyethylene and polypropylene. Polyethylene and polypropylene were degraded 9% and 4% by incubation for 26 days without pretreatment procedure. Various fatty acid compounds were identified from biodegraded polyethylene and polypropylene. Abstract: Petroleum-based plastic is a widely used commodity in modern living due to its extensive industrial and domestic applications. Polyethylene and polypropylene account for more than 50% of total plastic usage, and they resist decomposition in a natural environment. In this study, Lysinibacillus sp., isolated and identified as a novel strain, was investigated to decompose polyethylene and polypropylene. In the microbial cultivation medium without any physicochemical pretreatment, the Lysinibacillus sp. reduced the weight of polypropylene and polyethylene by approximately 4 and 9%, respectively, over 26 days. During the biodegradation of polyethylene and polypropylene, a rough surface increase was observed by scanning electron microscope (SEM) imaging. Moreover, various oxidation products containing CH2 groups produced from the decomposition of polyethylene and polypropylene were observed by GC–MS analysis. Results suggest that microorganisms can be used to degrade polyethylene and polypropylene without a physicochemical process. This can be a starting point for developing methods for remediating soil contaminated with plastics.